1997
DOI: 10.1007/s11746-997-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective acylation of Dl‐menthol in organic solvents by an immobilized lipase from Pseudomonas cepacia with vinyl propionate

Abstract: An effective lipase-catalyzed stereoselective transesterification of (±)-menthol in organic solvent with vinyl propionate as acylating agent is described. Immobilization by adsorption and the presence of molecular sieves improved the formation of (±)-menthyl propionate by lipase (PS-30) from Pseudomonas cepacia. The reaction time course, mole ratio of substrates, temperature, amount of enzyme, as well as the effect of various organic solvents, were examined for their influence on the enzymatic stereoselective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…The ee p decreased from 99.4% (25 • C) to 98.5% (50 • C). And it decreased significantly and lower than 99% when the temperature was more than 40 • C. The result was similar to Applied Biochemistry that with an immobilized lipase from Pseudomonas cepacia in stereoselective acylation of (±)-menthol with vinyl propionate, where the mole percentage yield of (−)-menthyl propionate increased but the stereoselectivity decreased as the reaction temperature increased [17]. Thus, considering the optical purity of the product and the point of view on green economy, a reaction temperature of 30 • C was selected for the next reactions.…”
Section: Figsupporting
confidence: 83%
See 3 more Smart Citations
“…The ee p decreased from 99.4% (25 • C) to 98.5% (50 • C). And it decreased significantly and lower than 99% when the temperature was more than 40 • C. The result was similar to Applied Biochemistry that with an immobilized lipase from Pseudomonas cepacia in stereoselective acylation of (±)-menthol with vinyl propionate, where the mole percentage yield of (−)-menthyl propionate increased but the stereoselectivity decreased as the reaction temperature increased [17]. Thus, considering the optical purity of the product and the point of view on green economy, a reaction temperature of 30 • C was selected for the next reactions.…”
Section: Figsupporting
confidence: 83%
“…Wu et al. reported that the lipase from P. cepacia gave a yield of 53.4% for (−)‐menthyl ester with an ee p of 99.1% at the substrate concentration of 0.5 M after 24 H of reaction ( Q = 11.1 mmol/L H). Persichetti et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The split was 25:1. For identification and quantification of unreacted fatty acids, unreacted menthol and menthyl esters, at first mixtures of these components in different concentrations were prepared using standard fatty acids, standard menthol, and standard menthyl esters prepared according to the method of Wu et al (7). Later these mixtures were analyzed directly without derivatizing the fatty acids by capillary gas chromatography under the same working conditions mentioned above in order to get response factors of reactants and products and to establish calibration curves for them.…”
Section: Methodsmentioning
confidence: 99%